Agência Lupa and the Selection of Sources in Fact-Checking About Covid-19 - Ribeiro Xavier, Tylcéia Tyza (2022)
This article is the result of the undergraduate final Project presented to the examining board from the Social Communication course with a degree in journalism, and aims to analyze the checks made by the fact-checking platform Agência Lupa, regarding the disinformation contents disseminated from March to August 2020 about covid-19, the period when the virus have arrived in Brazil, and then, the milestone of 100,000 deaths from the disease in the country. Six checks made by Lupa were selected, one for each of the chosen months. For the methodological process of this work, we used content analysis combined with a data collection protocol based on the concept and classification of sources.